Integrated marketing communication : advertising and promotion in a digital world - Juska, Jerome M. (New York: Routldge, 2022)
"Now in its second edition, this textbook explores the continuing transformation of advertising, sales promotion, and public relations functions within the marketing discipline. The content focuses on emerging new technologies, as well as established digital and legacy media, as the reader is guided through the process of developing and implementing a comprehensive Integrated Marketing Communication plan for companies, organizations, and brands. Clear, concise and practical, the book takes the reader through consumer, market, and competitive research; creative conceptualization; market segmentation, identification of a target audience, and brand positioning; as well as strategic decisions involving the timing, placement, and intensity of advertising, sales promotion, public relations, and brand visibility. The new edition emphasizes the importance of social media, website development, search engine optimization, mobile marketing, brand promotion events, and retail store connectivity. Updated to include more digital content with detailed international examples, this new edition adds four new chapters including IMC objectives, budgets, and metrics, legacy media planning, B2B marketing strategies, and innovative technologies with topics such as artificial intelligence, predictive analytics, synthetic media, virtual reality, and voice marketing. Upper-level undergraduate and postgraduate students will appreciate this lucid up-to-date text, as will business professionals in executive education and certificate programs. Experiential learning is provided with chapter assignments and a continuity case study woven into the textbook. The second edition is also accompanied by robust online resources, including PowerPoint slides, chapter videos, lecture notes, classroom exercises, digital flash cards, test banks, instructor resource book, and interactive template for preparing an IMC Plan"--
Revised edition of the author's Integrated marketing communication, 2017.
Includes bibliographical references and index.
Keywords: Internet advertising; Internet marketing